Promotion of improved cookstove in rural Bangladesh - Arif, Tahmid; Ashraf, Anik; Miller, Grant; Mobarak, Ahmed Mushflq; Akter, Nasima; Ali, ARM Mehrab; Sarkar, MA Quaiyum; Hildemann, Lynn; Dey, Nepal C; Rahman, Mizanur; Dwivedi, Puneet; Wise, Paul (BRAC, 2019)
This study aimed to explore the factors affecting the promotion of improved cookstove (ICS) to replace traditional stove and hence to combat indoor air pollution (lAP). The study was conducted in 58 randomly selected villages of Jamalpur sadar and Hatia upazilas (29 villages in each) in 2008. Both qualitative and quantitative methods were used. Focus group discussions were performed in each village to divide the villages in three equal clusters as well as Paras and listed the opinion leader of the villages. Fifty randomly selected households and nine households of the opinion leaders were surveyed in each village. Thus, a total of 3,080 households were selected for quantitative survey with pre-designed questionnaire. These households were also offered two types of ICSs - portable and with-chimney under different experimental conditions. Among those who adopted ICS as was offered usually chose portable res since they believed this would reduce fuel consumption while they chose 1es with chimney to reduce pollution. We found that households were usually aware of lAP but not so much so of the existence of res. But once they came to know about it through this survey, they would expect ICS to be better than traditional stoves in producing better tasting food, less smoke emissions, less cooking and fuel collection time, etc. When compared with those who did not know about ICS before, prior knowledge on ICS was found to be associated with greater share of people thinking res was better than traditional in terms of taste of food and smoke emission. In most cases financial constraints was stated as a reason for not to adopt an res. The adoption decision was also found to be highly responsive to price. On the other hand, opinion leaders appeared to have a stronger impact on households' decisions when the leaders decided against 1es as opposed to when they decided in its favour. Although this is a very product specific study the results can provide a guideline to understand similar constraints for many other improved technologies that exist but are not generally adopted.